Factors influencing implementation early initiation of breastfeeding (IMD ) in post partum mothers: A scoping review - Febriyani, Irma; Rokhanawati, Dewi (Journal of Health Technology Assessment in Midwifery, 2024)
Implementation of early initiation of breastfeeding (IMD) is the act of giving breast milk to babies within one hour after birth. In postpartum mothers, there are various factors that influence the implementation of IMD, such as the level of knowledge, education and support from the surrounding environment. A deeper understanding of these factors is essential to improve IMD implementation and promote optimal breastfeeding practices. To map evidence related to factors that influence the implementation of IMD in postpartum mothers. This type of research,  namely  Scoping Review, refers to the steps  of  Arksey  and  O'maley,  the framework  used is PEOS, the articles selected are articles from 2019 to 2023, articles in English and Indonesian and articles that focus on the  factors  that  influence  implementation  Early initiation of breastfeeding, in selecting articles using the Prisma Flow Chart Checklist, data  sources from journals were  accessed via the Pubmed, Wiley, and Google Scholar databases with the keywords (influencing factors) AND (early initiation of breastfeeding) which resulted  in  295  journals,  after  going through several stage  obtained  5 journals.  This research carried out a Critichal Appraisal according to the design in the research journal, namely cross-sectional Critical Appraisal. Based on 295 selected journals, only 5 articles were reviewed based on the inclusion criteria, Early Breastfeeding Initiation Has Various Factors that Influence the Success of Early Breastfeeding Initiation, namely Knowledge, Education, Attitude and Family Support. It is expected that this scope review will include further tracing of accessible databases to support this.